Timing of Tracheotomy in Mechanically Ventilated Critically Ill Morbidly Obese Patients - Ahmad Alhajhusain; Ailia W. Ali; Asif Najmuddin; Kashif Hussain; Masooma Aqeel; Ali A. El-Solh (Critical Care Research and Practice)
Background. The optimal timing of tracheotomy and its impact on weaning from mechanical ventilation in critically ill morbidly obese patients remain controversial. Methods. We conducted a retrospective chart review of morbidly obese subjects (BMI ≥ 40 kg/m2 or BMI ≥ 35 kg/m2 and one or more comorbid conditions) who underwent a tracheotomy between July 2008 and June 2013 at a medical intensive care unit (ICU). Clinical characteristics, rates of nosocomial pneumonia (NP), weaning from mechanical ventilation (MV), and mortality rates were analyzed. Results. A total of 102 subjects (42 men and 60 women) were included; their mean age and BMI were 56.3 ± 15.1 years and 53.3 ± 13.6 kg/m2, respectively. There was no difference in the rate of NP between groups stratified by successful weaning from MV (P=0.43). Mortality was significantly higher in those who failed to wean (P=0.02). A cutoff value of 9 days for the time to tracheotomy provided the best balanced sensitivity (72%) and specificity (59.8%) for predicting NP onset. Rates of NP and total duration of MV were significantly higher in those who had tracheostomy ≥ 9 days (P=0.004 and P=0.002, resp.). Conclusions. The study suggests that tracheotomy in morbidly obese subjects performed within the first 9 days may reduce MV and decrease NP but may not affect hospital mortality.